Modelling sexually deceptive orchid species distributions under future climates: the importance of plant-pollinator interactions - Tsiftsis, Spyros; Djordjević, Vladan (Scientific reports, 2020)
Biotic interactions play an important role in species distribution models, whose ignorance may cause an overestimation of species' potential distributions. Species of the family Orchidaceae are almost totally dependent on mycorrhizal symbionts and pollinators, with sexually deceptive orchids being often highly specialized, and thus the interactions with their pollinators are expected to strongly affect distribution predictions. We used Maxent algorithm to explore the extent of current and future habitat suitability for two Greek endemic sexually deceptive orchids (Ophrys argolica and Ophrys delphinensis) in relation to the potential distribution of their unique pollinator (Anthophora plagiata). Twelve climate change scenarios were used to predict future distributions. Results indicated that the most important factors determining potential distribution were precipitation seasonality for O. argolica and geological substrate for O. delphinensis. The current potential distribution of the two orchids was almost of the same extent but spatially different, without accounting for their interaction with A. plagiata. When the interaction was included in the models, their potentially suitable area decreased for both species. Under future climatic conditions, the effects of the orchid-pollinator interaction were more intense. Specifically, O. argolica was restricted in specific areas of southern Greece, whereas O. delphinensis was expected to become extinct. Our findings highlighted the significant role of plant-pollinator interactions in species distribution models. Failing to study such interactions might expose plant species to serious conservation issues.
Keywords: včely; Pollination; Flowers; biologická evoluce; zachování přírodních zdrojů; teoretické modely; Climate Change; zvířata; Orchidaceae; Biological Evolution; Models, Theoretical; Bees; opylení; klimatické změny; Conservation of Natural Resources; květy; Animals